Hot off the press! An update on most recent negotiations to improve the Plant Treaty's Multilateral System of Access and Benefit-sharing [webinar for CGIAR staff] - Halewood, Michael; Lopez Noriega, Isabel; Sackville-Hamilton, Nigel Ruaraidh; Rouard, Mathieu; Chiarolla, Claudio (2024)
International negotiations continued from 16-18 April 2024, to revise the Plant Treaty’s Multilateral System of Access and Benefit-sharing. While “nothing is agreed until everything is agreed”, as negotiators always like to say, there were some important breakthroughs during the meeting. In this webinar, CGIAR scientists provided an overview of this negotiating session’s most important outcomes, and their potential relevance to CGIAR Centers and Initiatives. This webinar builds on an earlier webinar ("Negotiations to improve the Plant Treaty's Multilateral System of Access and Benefit-sharing (a primer for CGIAR staff"), held on 20 March 2024, wherein the Plant Treaty Secretary and Co-Chairs of the negotiating working group provided an introduction to the history and progress of the negotiations.